Ocena zmian w transporcie kolejowym pasażerskim w województwie wielkopolskim = Assessment of changes in rail passenger in the region Wielkopolska - Nowak, Renata; Rabant, Hubert (Journal of Education, Health and Sport, 2016)
Nowak Renata, Rabant Hubert. Ocena zmian w transporcie kolejowym pasażerskim w województwie wielkopolskim = Assessment of changes in rail passenger in the region Wielkopolska. Journal of Education, Health and Sport. 2016;6(12):552-563. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.216358 http://ojs.ukw.edu.pl/index.php/johs/article/view/4099 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 754 (09.12.2016). 754 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.12.2016. Revised 12.12.2016. Accepted: 20.12.2016. Ocena zmian w transporcie kolejowym pasażerskim w województwie wielkopolskim Assessment of changes in rail passenger in the region Wielkopolska Renata Nowak, Hubert Rabant Uniwersytet Kazimierza Wielkiego w Bydgoszczy Streszczenie: Celem niniejszego artykułu jest przedstawienie oceny zmian w transporcie kolejowym pasażerskim na liniach normalnotorowych w województwie wielkopolskim. Do analizy zagadnienia wykorzystano badania ankietowe przeprowadzone na 8 stacjach kolejowych regionu (Poznań Główny, Kalisz, Konin, Piła Główna, Gniezno, Leszno, Wągrowiec i Krzyż Wielkopolski). Respondenci wyrażali opinię na temat funkcjonowania transportu kolejowego, powiązania z innymi gałęziami transportu oraz wpływu na gospodarkę regionalną. W artykule przedstawione zostały również uwarunkowania historyczne przemian sieci kolejowej województwa. Abstract: This article aims at presenting an assessment of the changes in rail passenger transport in the region Wielkopolska. For analysis of the issue there were used surveys conducted on 8 railway stations in the region (Poznań Główny, Kalisz, Konin, Piła, Gniezno, Leszno, Wągrowiec and Krzyż Wielkopolski). Respondents expressed an opinion on the functioning of railway transport, connections with other types of transport and the impact on the regional economy. The article presents the historical conditions of change of the railway network of the region. Słowa kluczowe: województwo wielkopolskie, transport kolejowy, badanie ankietowe Keywords: wielkopolska region, railway transport, questionnaire study